Experiencias Sobre Desempleo Profesional y su Relación con la Motivación, Expectativas y Frustración, Comprendidas desde las Narrativas de Jóvenes Egresados de Psicología (2023)
The objective of this research was to analyze the experiences of unemployment in the professional labor market when it lasted longer than one year, which may influence motivation, expectations and frustrations, understood from the narratives of young people between 23 and 30 years of age, graduates of the psychology career of the Antonio Nariño University.